2010
DOI: 10.1016/j.chemgeo.2009.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Trace-element geochemistry of mantle olivine and application to mantle petrogenesis and geothermobarometry

Abstract: Trace element compositions of olivine from 75 mantle rocks of diverse origin, including xenoliths from kimberlites, basaltic lavas and orogenic peridotites, were determined by laserablation ICP-MS to study systematic variations between mantle lithologies, partitioning mechanisms in olivine and the potential of olivine for geothermobarometry and petrogenic mantle processes. Samples were selected to provide a wide range of forsterite contents (89.1-93.4), equilibration temperatures and pressures (750-1450°C; 15-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
257
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(278 citation statements)
references
References 77 publications
15
257
0
6
Order By: Relevance
“…These features are consistent with derivation from mantle melts (Sato 1977;Sano et al 2002;de Hoog et al 2010). Low Cr contents in olivine (6 ppm) compared to other mantle-derived lherzolite examples (de Hoog et al 2010) is interpreted to reflect sequestering of Cr in phlogopite over olivine. The dunite xenolith also contains a whole rock signature which may be consistent with crustal contamination including LILE and LREE enrichment, and negative Nb, Ti and Y anomalies.…”
Section: Geoscience Canadasupporting
confidence: 65%
“…These features are consistent with derivation from mantle melts (Sato 1977;Sano et al 2002;de Hoog et al 2010). Low Cr contents in olivine (6 ppm) compared to other mantle-derived lherzolite examples (de Hoog et al 2010) is interpreted to reflect sequestering of Cr in phlogopite over olivine. The dunite xenolith also contains a whole rock signature which may be consistent with crustal contamination including LILE and LREE enrichment, and negative Nb, Ti and Y anomalies.…”
Section: Geoscience Canadasupporting
confidence: 65%
“…This indicates that Ti and H are being incorporated together as part of the same point defect, and that the formation of this defect is the dominant method of incorporating both Ti and H in the system studied. Note that Ti concentrations overlap the range found in natural mantle olivines (De Hoog et al 2010). Extrapolating the trend of H 2 O concentration vs. Ti concentration to anhydrous conditions gives a Ti [Ti] experiments conducted at variable a H2O .…”
Section: +mentioning
confidence: 99%
“…A number of studies have previously postulated that microbes preferentially attach themselves to active sites on dissolving mineral surfaces to harvest essential nutrients from the minerals (Hutchens et al, 2006;Bonneville, 2009Bonneville, , 2010Balland et al, 2010). Note that the dissolving San Carlos forsterite contains a large number of the elements required for microbial growth in trace quantities (De Hoog et al, 2010).…”
Section: The Long-term Dissolution Behavior Of Forsterite At Earth Sumentioning
confidence: 99%
“…The San Carlos forsterite sample used in this study was originally prepared by Pokrovsky and Schott (2000a and b), who reported that its composition is consistent with Mg 1.82 Fe 0.18 SiO 4 (Fo 91 ). San Carlos Olivine has been reported to contain numerous trace elements including ~40 ppm P (De Hoog et al, 2010). Transparent crystals 0.5 cm in size were handpicked, ground with an agate mortar and pestle, and sieved.…”
Section: Batch Reactor Experimentsmentioning
confidence: 99%